PENAWARAN TENAGA KERJA DAN FENOMENA BURUH PEREMPUAN - Siti Maria (FORUM EKONOMI, 2015)
The phenomenon of labor in East Kalimantan this raises a presumption that the level of wages not paid on the same level of labor productivity. Wage inequality with MPL can be assessed by examining some of the factors that influence the wage rate. Women who work in the formal sector tend to have high levels of education and skills, access to financial institutions, labor productivity and wage rates are also relatively high compared with women working in the informal sectorÂ Keyword: Labor, Women, Informal Sector